H. Tristram Engelhardt Junior: A Moral Friend and Moral Stranger - Po-Wah, Julia Tao Lai (Conatus - Journal of Philosophy, 2018)
This paper is a tribute to H.T. Engelhardt Jr. for the intellectual resources he provided to challenge cosmopolitan liberalism as the foundation for an overarching global bioethics in the post-modern world. It is a also a tribute to the moral pluralism and cultural diversity which he argued so forcefully in all his works and which have inspired the flourishing of fierce bioethical debates across the world, including in the non-Western and Asian societies.